2020
DOI: 10.1186/s12885-020-06885-3
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate anaplerosis is a mechanism of resistance to pharmacological glutaminase inhibition in triple-receptor negative breast cancer

Abstract: Background: Glutamine serves as an important nutrient with many cancer types displaying glutamine dependence. Following cellular uptake glutamine is converted to glutamate in a reaction catalysed by mitochondrial glutaminase. This glutamate has many uses, including acting as an anaplerotic substrate (via alpha-ketoglutarate) to replenish TCA cycle intermediates. CB-839 is a potent, selective, orally bioavailable inhibitor of glutaminase that has activity in Triple receptor-Negative Breast Cancer (TNBC) cell li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Upon AZD3965 treatment, proliferating cancer cells, but not nonmalignant cells, accelerated OCR linked to ATP production, hence their OXPHOS rates. Such increase could primarily result from inhibition of pyruvate export [ 53 ], but discrepancies between cancer and nonmalignant cells rather indicate that selective lactate export inhibition in cancer cells is a main contributor to the switch, notwithstanding a possible contribution of other available oxidative substrates (glucose, glutamine, lipids).…”
Section: Discussionmentioning
confidence: 99%
“…Upon AZD3965 treatment, proliferating cancer cells, but not nonmalignant cells, accelerated OCR linked to ATP production, hence their OXPHOS rates. Such increase could primarily result from inhibition of pyruvate export [ 53 ], but discrepancies between cancer and nonmalignant cells rather indicate that selective lactate export inhibition in cancer cells is a main contributor to the switch, notwithstanding a possible contribution of other available oxidative substrates (glucose, glutamine, lipids).…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, reducing cell culture medium nutrients to physiological levels also compromised the sensitivity of lung cancer cells to glutaminase inhibitors (137). Singleton et al found that CB-839 activity was significantly compromised in three dimensional spheroids assay compared with two dimensional monolayer culture in TNBC cells (138) The questions then arise: what is the molecular mechanism of glutaminase inhibition resistance and how could we overcome the therapy resisatnce? Firstly, as the most frequently used glutaminase inhibitors such as BPTES and CB-839 are GLS1 selective, the resistance to glutaminase inhibition may be due to the differential expression of GLS1 and GLS2 in cells, as demonstrated in luminal and basal-like breast cancer cells (78).…”
Section: Glutaminase Inhibitor Based Therapeutic Strategymentioning
confidence: 99%
“…Application of a pan-glutaminase inhibitor 968 suppresses BPTES-resistant breast cancer growth. Importantly, a number of studies have demonstrated that glutaminase inhibition could be rescued by alternative metabolic pathways, such as glycolysis and fatty acid oxidation (FAO) (130,138,142). A combinatorial strategy may help to overcome glutaminase inhibition resistance.…”
Section: Glutaminase Inhibitor Based Therapeutic Strategymentioning
confidence: 99%
“…Strictly speaking, Gln starvation therapy by targeting GLS is to block Gln consumption (utilization) rather attacking Gln itself. Treating breast cancer cells with GLS inhibitors decreases downstream metabolites of Glu, including those in the TCA cycle that requires anaplerosis for replenishment [20].…”
Section: Glutamine Starvationmentioning
confidence: 99%